2015
DOI: 10.1159/000441024
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Modulates Cerebral and Serum Degradation Products from Excess Calpain Activation following Prenatal Hypoxia-Ischemia

Abstract: Preterm infants suffer central nervous system (CNS) injury from hypoxia-ischemia and inflammation - termed encephalopathy of prematurity. Mature CNS injury activates caspase and calpain proteases. Erythropoietin (EPO) limits apoptosis mediated by activated caspases, but its role in modulating calpain activation has not yet been investigated extensively following injury to the developing CNS. We hypothesized that excess calpain activation degrades developmentally regulated molecules essential for CNS circuit fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 65 publications
(105 reference statements)
7
49
0
Order By: Relevance
“…Accurate use of serum biomarkers requires an understanding of their biological basis in the CNS, which is probably complex in the developing brain. 37,39 In the present study we showed that cortical calpain activity is elevated 3 days after a CCI delivered on P12, as shown by increases in αII-SDPs, KCC2-DPs, and GFAP-DPs. The observed elevation in αII-SDPs is consistent with findings from other TBI studies.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Accurate use of serum biomarkers requires an understanding of their biological basis in the CNS, which is probably complex in the developing brain. 37,39 In the present study we showed that cortical calpain activity is elevated 3 days after a CCI delivered on P12, as shown by increases in αII-SDPs, KCC2-DPs, and GFAP-DPs. The observed elevation in αII-SDPs is consistent with findings from other TBI studies.…”
Section: Discussionsupporting
confidence: 62%
“…29,37,39 These mechanisms of action support the rationale that an extended dosing regimen with neuroprotective doses of EPO is probably necessary to alter recovery after TBI. In particular, because exogenous EPO promotes oligodendroglial lineage survival and maturation 38 and because recovery of the oligodendroglial lineage extends over 3 months after CCI injury in mice, 19 EPO treatment should theoretically benefit white matter recovery over a protracted period.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…4–12% Criterion-XT precast gels (Bio-Rad, Hercules, CA, 345-0124) were loaded with 30μg of protein per well. Following electrophoresis, protein was transferred to polyvinylidene fluoride membranes (PVDF; Bio-Rad, 1620177) that were blocked in milk/1xTris Buffered Saline with Tween 20 (TBS-T) and incubated in anti-MBP (1:1000; EMD Millipore, AB980) or anti-actin (1:5000; Sigma-Aldrich, A5441) at 4°C overnight as previously published (Jantzie et al 2014; Jantzie et al 2016). The following day, membranes were incubated in species appropriate HRP-conjugated secondary antibodies (1:5000; Thermo Scientific, Waltham MA, 62460) at room temperature for 1 hour, after which, membranes were washed, incubated with femto-west electrochemiluminescent substrate (ECL; Thermo Scientific, 37075), and developed using the chemiluminescent function of a GE-LAS 4000 Digital image reader (GE Healthcare Life Sciences, Chicago, IL).…”
Section: Methodsmentioning
confidence: 99%